On interpreting India's past - Sen, Amartya, 1933- (Calcutta : Asiatic Society, 1996)
Revision of the first Abha Maiti memorial lecture delivered at the Asiatic Society on 20 March 1995.
Includes bibliographical references
Keywords: Nationalism -- India